ANALYSIS OF INVESTMENT RISK IN MALUKU PROVINCE USING MEAN-VARIANCE APPROACH ON LOCAL OWN-SOURCE REVENUE (PAD) - Bakarbessy, Lusye; Talakua, Mozard Winston; Ilwaru, Venn Yan Ishak (VARIANCE: Journal of Statistics and Its Applications, 2025)
This study aims to analyze investment risks in Maluku Province using the Mean-Variance approach on the Local Own-Source Revenue (PAD) data. The method used in this study is a quantitative analysis of time-series data on PAD from 2015 to 2022. The mean-variance model is used to calculate the rate of return and risk of each PAD component and to construct an efficient frontier as a basis for optimal decision-making. The results show that the regional tax PAD component offers a high rate of return with relatively low risk, potentially making it a stable source of revenue for local governments. These findings provide a basis for optimizing PAD allocation to improve fiscal stability and the sustainability of regional development.